The Feasibility of “Scanara” Ready-to-Wear Clothing with QR Code Technology - Novitasari, Neny; Nurmasitah, Sita (Journal of Creativity Student, 2025)
The development of digital technology has driven innovations in the fashion industry, including the integration of Quick Response (QR) codes into clothing products as an interactive information medium. This study aims to determine the feasibility of the design and products of the “Scanara" Ready-to-Wear Fashion, as well as the feasibility of QR Code media with embroidery techniques applied as a means of delivering digital information. The research method employs a descriptive percentage approach, utilizing an assessment instrument compiled based on theoretical studies related to fashion design, construction, aesthetics, comfort, and interactive media. The assessment was conducted by six experts, comprising three fashion experts and three media experts. Data were analyzed using quantitative descriptive techniques by calculating the feasibility percentage based on the obtained score and the maximum score. The results showed that the “Scanara” ready-to-wear fashion obtained a feasibility percentage of 82.5% and was categorized as "Very Feasible". Meanwhile, the QR Code media achieved a feasibility score of 96.25% with the category of "Very Feasible". These Findings indicate that the integration of QR Code technology with embroidery techniques not only improves the informative and aesthetic functions of fashion but also supports the development of modern, interactive, and adaptive fashion products. Thus, the developed fashion and digital media are declared very feasible for use, production, and further development.